2011
DOI: 10.3748/wjg.v17.i10.1267
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein thrombosis and arterioportal shunts: Effects on tumor response after chemoembolization of hepatocellular carcinoma

Abstract: TACE may be exploited safely for palliative tumor control in patients with advanced unresectable HCC; however, tumor response is significantly affected by the presence or absence of PVT and APS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…Last, arterioportal shunts have been commonly observed in association with HCC, likely related to tumor vascular invasion [31, 32]. Vogl et al [33] reported a significantly increased rate of progression after TACE by MRI volumetric measurements compared with patients without arterioportal shunting.…”
Section: Discussionmentioning
confidence: 99%
“…Last, arterioportal shunts have been commonly observed in association with HCC, likely related to tumor vascular invasion [31, 32]. Vogl et al [33] reported a significantly increased rate of progression after TACE by MRI volumetric measurements compared with patients without arterioportal shunting.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not vascular resection of the portal vein bifurcation is necessary remains debated [70,71]. It has been shown that preoperative TACE could improve long-term outcome in patients with portal involvement [72,73].…”
Section: Assessment Of Liver Functionmentioning
confidence: 99%
“…TARE with its microembolic properties has been favored for the treatment of HCC with PVTT. TACE can also be performed safely for palliative tumor control in patients with advanced HCC with portal vein thrombosis [ 97 ] .…”
Section: Treatment Options In Hccmentioning
confidence: 99%